Optimalisasi Jalur Terpendek Menggunakan Algoritma Genetika - jasmani jasmani; Ali Mahmudi (J-INTECH ( Journal of Information and Technology), 2023)
Traffic problems in a big city are quite complicated to deal with. Various traffic problems such as traffic jams, accidents and others. One of the problems included in the traffic problem is the search for a path or route to a location. Pathfinding is very necessary for road users who do not know which way to go to get to their destination in a city. Especially for road users who are visiting the city for the first time. It is also possible for residents of big cities themselves who do not know by heart or do not know which route to take to get to a place they want. Time and cost savings are other factors that require road users to find the shortest path to get to their destination more quickly. Because of that, the search for the shortest path becomes a problem that deserves to be solved computerized with artificial intelligence (Artificial Intelligence). In the case that we try to discuss using the genetic algorithm method.